2007
DOI: 10.1213/01.ane.0000221469.24319.49
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guidance for Lateral Midfemoral Sciatic Nerve Block: A Prospective, Comparative, Randomized Study

Abstract: Block of the sciatic nerve at the midfemoral level is usually performed using nerve stimulation techniques. We investigated the efficacy of ultrasound, combined with nerve stimulation, to locate and block the sciatic nerve at the lateral midfemoral level compared to nerve stimulation alone. Sixty-one patients scheduled for foot and ankle surgery were enrolled in this prospective, randomized study. Thirty patients underwent a lateral block of the sciatic nerve at the midfemoral level guided by ultrasound (group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(64 citation statements)
references
References 25 publications
0
61
0
2
Order By: Relevance
“…The usefulness of regional nerve block under US guidance has been reported by several authors [2,5,6,12]. It has numerous advantages, such as precise targeting, less needle pain due to the short procedure duration, more rapid anesthesia, higher anesthesia success rate, fewer postoperative complications, and extended postoperative pain-free duration.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of regional nerve block under US guidance has been reported by several authors [2,5,6,12]. It has numerous advantages, such as precise targeting, less needle pain due to the short procedure duration, more rapid anesthesia, higher anesthesia success rate, fewer postoperative complications, and extended postoperative pain-free duration.…”
Section: Discussionmentioning
confidence: 99%
“…50,59,60 Ultrasonography, in combination with neurostimulation, has been successfully used as an adjunct in one RCT pertaining to the lateral midfemoral approach. 55 Further RCTs are required to determine its role in other approaches. Finally, the best method for anesthesia of the posterior tibial nerve is a neurostimulation-guided injection around the medial malleolus.…”
Section: Discussionmentioning
confidence: 99%
“…In the second RCT, adjunctive neurostimulation was compared to neurostimulation combined with echoguidance. 55 In 61 patients undergoing foot and ankle surgery, Domingo-Triado et al 55 found that, with the combination of the two modalities, fewer attempts were required (1 vs 2; P = 0.001) and a denser sensory block was achieved (P = 0.01). However performance, onset and offset times were not significantly different between the two groups.…”
Section: Techniquesmentioning
confidence: 99%
“…Domingo-Triado ve ark. 'nın [16] , alt ekstremite cerrahisi uygulanan 61 hasta üzerine yapılan çalışmala-rında, ilk girişimde siyatik sinirin konumunu bulma başarıları karşılaştırılmış, ultrason grubundaki başarı, nörostimülator grubundakine göre istatistiksel olarak anlamlı derecede yüksek bulunmuş (%76.6 versus %41.9; p<0.001). Yine aynı çalışmada, duyusal blok kaliteleri karşılaştırılmış, ultrason grubunda nörostimülator grubuna göre istatistiksel olarak anlamlı derecede yüksek bulunmuş (p<0.001).…”
Section: Cox Ve Arkunclassified